Mission to Pluto : the first visit to an ice dwarf and the Kuiper Belt - Carson, Mary Kay (Scientists in the field., 2016)
Explores the history of the New Horizons' spacecraft mission to Pluto and the Kuiper belt, discussing how the NASA team pulled it off and the discoveries the probe has made.